A BRIEF ANALYSIS OF EDUCATIONAL POLICIES IN CHINA AND PAKISTAN DURING COVID-19 - Fuad Ali, Khowaja; Lin, Jing; Peng, Yanmu; Su, Manyi (INTI International University, 2022)
The purpose of the research is to identify challenges arising from the two policies of Technology Advancement and Online education with element of school management in the context of a higher education institution in China and Pakistan, and to devise effective interventions to address the issues. The study was conducted with teachers chosen from random institutions followed by a semi-structured interview. The findings from the policy analysis of China indicated that internet connection, insufficient ICT-literacy, lagging appropriate pedagogical approaches are the three challenges for Technology Advancement. As for the online education, inability to shift to a virtually managerial mode and limited technological capabilities are the major issues in China. Whereas, in Pakistan, the occurrence of the COVID- 19 has exposed many deficiencies in policies, such as inadequate infrastructure construction, high drop-out rate, improper allocation of educational resources, and etc. Therefore, a nationguided network infrastructure construction, provision of ICT-literacy training, and updated technology-based pedagogy is proposed to mitigate the challenges of the first policy; while a well-developed framework of virtual management and related training sessions can be provided by educational authorities to address the issue of the second policy of China. On the other hand, based on the policy changes by Pakistani government before and during the pandemic, this paper studies and discusses the problems and puts forward corresponding solutions in promoting the development of online education and educational technology in Pakistan. The purpose of this paper is to provide feasible suggestions for both countries technological industry, relevant enterprises, and national education departments.